Achieving a chapter (prayer conditions) in the Sunni talents book explanation of the urban introduction of Sheikh Said Baishen - Al-Sagaf, Mohammed Jamal Mohammed (Journal of Islamic Sciences, 2024)
Through this scientific research, the researcher sought to highlight the achievement of a part of a distinguished jurisprudential scientific book of the Aishen label: The Book of Sunni Talents Explained the Urban Introduction.Our objective in this research is to work towards achieving a chapter of this book in order to complete its full realization and dissemination of the distinguished scientific legacy of civilization. in addition to making an effort to make the most of this unique book, The problem of research was the quest to know Sheikh Baashan, his jurisprudence, his writing of Sunni talents and his jurisprudence in the investigative part And we came up with the result of this research to introduce the sign to living and writing his Sunni talents, In addition to deciphering the verified part of that book, the researcher has conducted his investigation work by attributing Quranic verses to her wall, The graduation of prophetic hadiths and commentary on some questions of jurisprudence. In this research, the researcher used the descriptive and historical curriculum. The research was divided into researchers: The first research introduces Sheikh Al-Marah Baashan and his book Sunni talents, and the second research achieves (prayer contraindications) of the book Prayer of Sunni Talents Explanation of the Urban Introduction.
Keywords: Sunni Talent; Explanation Introduction; Prayer Contraindications; Urban Introduction; Sign Baishen